The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s40538-021-00209-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Meloidogyne javanica parasitism on soybean development and chemical composition

Abstract: Background Soybean is a major economic crop worldwide, but its yield and quality are greatly affected by root-knot nematode infection. This study aimed to assess the effects of Meloidogyne javanica parasitism on soybean growth, yield, and quality. Soybean plants were inoculated with 0, 1000, 2000, or 4000 eggs + second-stage juveniles (J2) of M. javanica and evaluated for vegetative and nematode parameters. Grains from each treatment were analyzed for yield, proximate composition, total phenoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 36 publications
3
9
0
Order By: Relevance
“…Castanheira et al. (2021) reported a significant soybean growth reduction in shoot height and root length caused by M. javanica , which is consistent with the present study. The nine soybean varieties tested exhibited a severe reduction in shoot growth attributed to inadequate water and nutrient supply to the areal plant part that resulted from the damage caused to the root system (Escobar et al., 2015).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Castanheira et al. (2021) reported a significant soybean growth reduction in shoot height and root length caused by M. javanica , which is consistent with the present study. The nine soybean varieties tested exhibited a severe reduction in shoot growth attributed to inadequate water and nutrient supply to the areal plant part that resulted from the damage caused to the root system (Escobar et al., 2015).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the length of the roots decreased as the number of galls and final population increased. Similar findings were reported by Nora et al (2020) and Balardin et al (2022), which found a significant decrease in the yield of soybean cultivars with an increase in the number of galls and final population of M. javanica that can negatively affect pod number and grain weight of soybean (Castanheira et al, 2021).…”
Section: F I G U R Esupporting
confidence: 89%
See 1 more Smart Citation
“…Plant height was measured three times: 2, 4 and 5 weeks after sowing (WAS) of soybean seeds and 2, 4 and 5 weeks after transplanting (WAT) of tomato seedlings. The plant height data were used to calculate the area under plant height progress curve (AUHPC) using the formula analogue to that of area under disease progress curve or AUDPC [19] as in equation (1).…”
Section: Evaluation Of Plant Response and Nematode Parametersmentioning
confidence: 99%
“…Soybean and tomato are globally important and major economic crops worldwide due to their high nutritive value. Because of its high oil content and high-quality proteins, soybean is used in a variety of ways in both human and animal diets [1]. Tomato, on the other hand, is a rich source of vitamins and minerals, which are important micronutrients in the diet of humans [2].…”
Section: Introductionmentioning
confidence: 99%